DAMPAK PERTUMBUHAN PENDUDUK TERHADAP PERTUMBUHAN EKONOMI DAN KELUARGA SEJAHTERA DI PROVINSI KALIMANTAN TIMUR - Rochaida, Eny (FORUM EKONOMI, 2016)
Development can be push by population as a subject of the development it self, and economic growth will be rise up if that population have a hight quality on productivity . But if the big population has low productivity it can make a problem not only in the population, but through the social economic condition. In this case population become a burden of development, it make the economic development run slowly because lack of population contribution in economy it self. In many theory that economic growth suggested will followed with create much employment opportunities, in the other hand population can involve as labor in that economic development. They will have income and that condition can be increasing his family welfare.Keyword: Population Growth, Economic Growth and Family Welfare